100 YEARS OF VITAMIN D: Dose–response for change in 25-hydroxyvitamin D after UV exposure: outcome of a systematic review. Issue 10 (15th October 2021) - Webb, Ann R; Alghamdi, Rehab; Kift, Richard; Rhodes, Lesley E
Abstract : A systematic review of publications addressing change in vitamin D status (25-hydroxyvitamin D (25OHD)) after exposure to UV radiation identified 2001 independent peer-reviewed publications. Of these, 21 used artificial sources of UV radiation, met all inclusion criteria and were quality assured; 13 publications used solar radiation and met sufficient inclusion criteria to be retained as supporting evidence; 1 further included publication used both solar and artificial sources. The review consistently identified that low dose, sub-erythemal doses are more effective for vitamin D synthesis than doses close to a minimum erythema dose; increasing skin area exposed increases the amount of vitamin D synthesised although not necessarily in a linear manner; constant dosing leads to a dose-dependent plateau in 25OHD, and dose–response is greatest at the start of a dosing regime; there is a large interpersonal variation in response to UV exposure. Fourteen of the studies using artificial sources of radiation were used to determine a dose–response relationship for change in 25OHD on whole-body exposure to repeated sub-erythemal doses of UV radiation, taking the form Δ25OHD (nmol/L) = A ln(standard vitamin D dose) + B. This helps quantify our understanding of UV as a source of vitamin D and enables exposure regimes for safe synthesis of vitamin D to be assessed. Specific studies of people with pigmented skin (Fitzpatrick skin types 5 and 6) were rare, and this dose–response relationship is only applicable to white-skinned individuals as skin type is a determinant of response to UV radiation. Findings provide information for vitamin D guidance updates.